Population Pharmacokinetics Analysis of Amikacin Initial Dosing Regimen in Elderly Patients - Hideo Kato; Suzanne L. Parker; Jason A. Roberts; Mao Hagihara; Nobuhiro Asai; Yuka Yamagishi; David L. Paterson; Hiroshige Mikamo (MDPI AG, 2021)
There are limited data of amikacin pharmacokinetics (PK) in the elderly population. Hence, we aimed to describe the population PK of amikacin in elderly patients (>70 years old) and to establish optimized initial dosing regimens. We simulated individual maximum concentrations in plasma (Cmax) and minimal concentrations (Cmin) for several dosing regimens (200-2000 mg every 24, 48, and 72 h) for patients with creatinine clearance (CCr) of 10-90 mL/min and analyzed efficacy (Cmax/minimal inhibitory concentration (MIC) ≥ 8) for MICs of 4, 8, and 16 mg/L and safety (Cmin < 4 mg/L). A one-compartment model best described the data. CCr was the only covariate associated with amikacin clearance. The population PK parameter estimates were 2.25 L/h for clearance and 18.0 L for volume of distribution. Dosing simulations recommended the dosing regimens (1800 mg) with dosing intervals ranging 48-72 h for patients with CCr of 40-90 mL/min based on achievement of both efficacy for the MIC of 8 mg/L and safety. None of the dosing regimens achieved the targets for an MIC of 16 mg/L. We recommend the initial dosing regimen using a nomogram based on CCr for an MIC of ≤8 mg/L in elderly patients with CCr of 40-90 mL/min.